The Jurisprudential Methodology of Imam Al-Kawashi in Presenting Schools of Islamic Law through His Exegesis(Al-Talkhiṣ fi Tafsir al-Qurʾan al-Athim ) - Rihab Abdul Aziz Ali; Rawa’ Izz al-Din Bassas (Islamic Sciences Journal, 2025)
ABSTRACT This research, entitled "The Jurisprudential Methodology of Imam Al-Kawashi in Presenting Schools of Islamic Law through His Exegesis Al-Talkhiṣ fi Tafsir al-Qurʾan al- Aẓim," comprises an introduction and two chapters. The Introduction addresses the significance of the topic, the research methodology, the research plan, and a preliminary overview. Chapter One covers: 1. The definition of jurisprudential methodology and its types. 2. A biographical introduction to Imam Al-Kawashi. Chapter Two analyzes Imam Al-Kawashi’s methodology in presenting jurisprudential schools (madhahib) through his exegesis. This is examined via numerous fiqh issues he addressed in interpreting ayat al-ahkam (Qurʾanic legal verses), Al-Kawashi meticulously cites opinions from juristic schools and traditions outside his own Shafi i madhhab, employing diverse approaches to present and critique them. He identifies positions aligned with or divergent from the Shafi i school and occasionally performs tarjih (weighing of evidence) between conflicting views. The study concludes with a summary of findings.